Eksplorasi dan Deskripsi dan Kunci Determinasi Musuh Alami Hama Kutu Kepik (Vatiga illudens Drake 1922) (Hemiptera: Tingidae) dari Pertanaman Singkong (Manihot esculenta) di Kabupaten Banyumas, Provinsi Jawa Tengah: Exploration and Description of Potential Natural Enemies of Aphids (Vatiga illudens Drake 1922) (Hemiptera: Tingidae) and Insects Associated with Cassava Cultivations in Banyumas Regency, Central Java Province - Agus Suroto; Tarjoko Tarjoko; Eka Oktaviani; Alifia Khairunnisa (Gontor Agrotech Science Journal, 2024)
The invasion of the ladybug (Vatiga illudens) has started a new chapter in Indonesia, with the first report of this pest in East Java Province in 2021. As a pest that attacks cassava plants, this pest is a threat to cassava plantations, one of which is in Banyumas District, Central Java Province. It is necessary to identify potential natural enemies that can become biological agents that suppress pest populations in the field and insects associated with cassava cultivations to control the pest and anticipate losses due to decreased production of cassava plants in the Banyumas District. This study aimed to explore and describe the natural enemies of ladybug pests and insects associated with cassava cultivations in the Banyumas District. The research was conducted in September 2022-January 2023 in seven cassava cultivation locations in Banyumas District. Samples of pests and or natural enemies were collected using a purposive random sampling method. The results showed a community of potential natural enemies of V. illudens and insects associated with cassava cultivations from the Orders Hemiptera, Diptera, Orthoptera, Coleoptera, and Araneae. The Results showed that 15 species act as potential natural enemies, eight species as pests, and two species as none of them (neutral).